Study of waist cercumference in Obesity Related Hypertension with Non-obesity Related Hypertension Without not Diagnosis Other Diseases (Journal of Pharmaceutical Negative Results, 2022)
The aim of our study is to find the relationship between waist circumference and obesity associated with high blood pressure and non-obese people associated with high blood pressure and to know the effect of waist circumference on pressure in the presence and absence of obesity, based on people diagnosed with high pressure without the presence of any other disease. The total number of participants is 120 sick participants. and healthy. Where we made a comparison between several groups, where the groups of obese people associated with high blood pressure and non-obese people associated with high blood pressure had an increase in waist circumference, as it was high pressure with waist circumference regardless of whether they were obese or otherwise Al-immamain Al-Kadhimayn Hospital, Baghdad, Iraq.The sensitivity analysis indicated a consistent trend between waist circumference and new-onset hypertension in all BMI categories. This study suggested high waist circumference as an independent risk factor for new-onset hypertension based on a nationwide cohort of adults aged ≥18 years old. Our results supported that waist circumference should be routinely measured.